Новітні технології маркетингових досліджень та аналізу ринку - Дума, О. І.; Мельник, М. С.; Duma, O. I.; Melnyk, M. S. (Видавництво Львівської політехніки, 2021)
На сучасному етапі все актуальнішими для успішності підприємств стають маркетингові дослідження. Проведення маркетингових досліджень знижує ризик прийняття неправильних рішень під час аналізу та розроблення маркетингових стратегій, планування і контролю маркетингової діяльності. Наведено огляд виникнення маркетингових досліджень, досліджено новітні методи маркетингових досліджень, їхні переваги та недоліки, можливість їх використання на різних етапах маркетингової діяльності. Систематизовано наукові підходи до трактування понять “маркетингові дослідження”, “методи маркетингових досліджень”. Проаналізовано новітні методи маркетингових досліджень, які передбачають широке використання AI (штучний інтелект), Big Data, ML, TRI*M. Проаналізовано також реалізацію методів маркетингових досліджень на основі Big Data, AI, ML, кейси із використанням новітніх методів маркетингових досліджень.

Nowadays, marketing research is increasingly important for the success of enterprises. Conducting marketing research reduces the risk of making wrong decisions in the analysis and development of marketing strategies, planning and control of marketing activities. The article provides an overview of the emergence of marketing research, explores the latest methods of marketing research, their advantages and disadvantages, the possibility of its application at different stages of marketing activities. Scientific approaches to the interpretation of the concepts “marketing research”, “methods of marketing research” are systematized. The latest methods of marketing research that widely use AI, Big Data, ML, TRI*M, have been studied. The technologies of mobile advertising, areas of use of artificial intelligence, the essence and features of the formation of Big Data and machine learning were researched in the article. The benefits of using artificial intelligence, big data and machine learning to conduct marketing research were researched in the article. Analytical materials are confirmed by cases from the practice of marketing research. All research outcomes were proved by cases of Independent Media, TNS Ukraine, British Council, Chat fuel and Coca-Cola. The scheme of the marketing research process is supplemented by the possibilities of applying the latest technologies, which are grouped by stages. Any marketing research is a sequence of steps. Each of them uses a set of tools that provide collection, processing and analysis of data about the target market, customers, or economic processes. Each of these stages can be implemented using the modern technologies that are widely used in various spheres of human life. The directions of application the artificial intelligence, Big data, machine learning for carrying out office researches, field researches, pilot researches and a method of focus groups are offered. The analysis of realization of methods of marketing researches on the basis of Big Data, AI, ML is carried out.
Modern technologies of marketing research and market analysis
Keywords: маркетингові дослідження; вивчення клієнта; процес маркетингових досліджень; технології маркетингових досліджень; штучний інтелект; фокус-група; машинне навчання; великі дані; marketing research; customer insight; marketing research process; marketing research technologies; artificial intelligence; focus group; machine learning; big data; 658.8.012.12